Thermotropic interface and core relaxation dynamics of liquid crystals in silica glass nanochannels: a dielectric spectroscopy study. Issue 34 (14th September 2015) - Całus, Sylwia; Borowik, Lech; Kityk, Andriy V.; Eich, Manfred; Busch, Mark; Huber, Patrick
<x xml:space="preserve">Abstract</x> We report dielectric relaxation spectroscopy experiments on two rod-like liquid crystals of the cyanobiphenyl family (5CB and 6CB) confined in tubular nanochannels with 7 nm radius and 340 micrometer length in a monolithic, mesoporous silica membrane.